Effectiveness Evaluation of Anthelminthics (Albendazole, Ivermectin and Levamisole) in a Breeding Stock Sheep Farm - Mitchaothai, Jamlong; Lukkananukool, Achara (Journal of Mahanakorn Veterinary Medicine, 2022)
The current study was aimed to evaluate effectiveness of anthelminthics; albendazole, ivermectin and levamisole in a breeding stock White Dorper sheep farm. Totally, 29 White Dorper sheep were included in this study and then allocated into 4 groups which were Control, Albendazole, Ivermectin and Levamisole for 6, 7, 8 and 8 animals, respectively. Dose (route of administration) of 10 (oral), 0.2 (subcutaneous) and 8 (subcutaneous) mg/kg BW was applied for the sheep in the group of Albendazole, Ivermectin and Levamisole, respectively. Fecal samples were collected individually from the experimental sheep at day 0, 7, 14, 28, 42 and 56 days after the start of the experiment. Quantity of helminth egg was determined by the McMaster technique and expressed as egg count per gram or EPG. Percentage of reduction of helminth eggs was calculated at different times after the start of the study. Fecal egg count reduction (FECR) was also calculated to determine anthelmintic resistance occurrence. The results showed that strongyle and strongyloides egg types found, with mainly strongyle egg type (86.21%) and an average of 3.55±0.11 log10 EPG+1 at the start of the study. After anthelmintic administration, levamisole significantly lowered (P<0.05) quantity of helminth eggs at day 7 (81.98% of reduction) and day 14 (90.19% of reduction) after anthelmintic administration. In the mean times, albendazole and ivermectin had effectiveness of 2.18% – 35.78% for helminth egg reduction at day 7 and 14 after anthelmintic administration. The value of FECR at 7 and 14 days after de-worming indicated anthelmintic resistance for albendazole and ivermectin, but gastro-intestinal helminths of the sheep were susceptible to levamisole with rather high effectiveness of levamisole (FECR = 99.92). Therefore, levamisole had high effectiveness for gastro-intestinal helminth control of sheep in the studied farm.